2004
DOI: 10.1093/hmg/ddi024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of the events leading to inactivation of the FMR1 gene

Abstract: The analysis of a lymphoblastoid cell line (5106), derived from a rare individual of normal intelligence with an unmethylated full mutation of the FMR1 gene, allowed us to reconstruct the chain of molecular events leading to the FMR1 inactivation and to fragile X syndrome. We found that lack of DNA methylation of the entire promoter region, including the expanded CGG repeat, correlates with methylation of lysine 4 residue on the N-tail of histone H3 (H3-K4), as in normal controls. Normal levels of FMR1 mRNA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 38 publications
5
137
1
Order By: Relevance
“…31 Here, we report the molecular epigenetic characterization of cell lines established from two newly identified, apparently normal individuals with an unmethylated full mutation, belonging to distinct FXS families. These cell lines showed molecular and epigenetic characteristics similar to those previously observed in the 5106 cell line, 27 suggesting the existence of a common mechanism as the basis of this rare phenomenon. The discovery of this mechanism may be important in view of therapeutic attempts at converting methylated into unmethylated full mutations, restoring the expression of the FMR1 gene.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…31 Here, we report the molecular epigenetic characterization of cell lines established from two newly identified, apparently normal individuals with an unmethylated full mutation, belonging to distinct FXS families. These cell lines showed molecular and epigenetic characteristics similar to those previously observed in the 5106 cell line, 27 suggesting the existence of a common mechanism as the basis of this rare phenomenon. The discovery of this mechanism may be important in view of therapeutic attempts at converting methylated into unmethylated full mutations, restoring the expression of the FMR1 gene.…”
Section: Introductionsupporting
confidence: 78%
“…Furthermore, the acetylation status of histones H3 and H4 and the methylation of H3-K9 was similar to FXS cell lines, whereas methylation of H3-K4 was like that of normal controls. 27 In FXS males with a mosaicism of methylated and unmethylated full mutation alleles, FMR1-mRNA levels were found elevated relative to normal controls, suggesting that the CGG expansion per se is not an impediment to transcription. 4 Elevated FMR1 RNA levels and reduced Fmrp were also described in a mouse model with an unmethylated Fragile X full mutation.…”
Section: Introductionmentioning
confidence: 95%
“…These include fragile X syndrome, in which lossof-function in FMR1 12 leads to intellectual disability. 13 The most common mechanism leading to fragile X syndrome is a CGG trinucleotide repeat expansion in the promoter region of the FMR1 gene leading to methylation of the promoter of the gene, with subsequent silencing of transcription and the absence of the encoded product FMRP, 14 which is important for synaptic plasticity and synaptic protein synthesis. 15,16 However, other loss-of-function mutations, including deletions, missense mutations and splice-site mutations, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Very few FXS patients have deletions or point mutations of the FMR1 gene [DeBoulle et al, 1993;Collins et al, 2010], resulting anyhow in FMRP loss-of-function. Finally, a rare class of FMR1 alleles is represented by unmethylated full mutations (UFM) that have been exceptionally reported in phenotypically normal males who have a CGG expansion over 200 repeats completely devoid of cytosine methylation [Smeets et al, 1995;Pietrobono et al, 2005;Tabolacci et al, 2008a]. The characterization of cell lines derived from these individuals has revealed that FMR1 promoter DNA is completely unmethylated (in both the CGG expansion and the FMR1 CpG island), transcription is increased (as in premutation carriers), FMRP levels are approximately 30-40% compared to normal (due to ribosome stalling on the expanded FMR1 mRNA [Feng et al, 1995]) and histone marks are similar to those of euchromatin (acetylation of histones 3 and 4, methylation of lysine 4 on histone 3 and di-methylation of lysine 27 on histone 3) with the exception for partial methylation of lysine 9 of histone 3 (H3K9).…”
Section: Fragile X Syndromementioning
confidence: 99%
“…The main epigenetic status of normal, FXS and UFM alleles is summarized in Figure 2. As discussed by Pietrobono et al [2005], these rare individuals suggest that the CGG expansion somehow causes a cascade of events (deacetylation of histones 3 and 4, methylation of H3K9, DNA methylation and eventually demethylation of H3K4) but, for unknown reasons, UFM carriers cannot complete the silencing process and maintain an active FMR1 locus.The exact timing in which DNA methylation is established is also unknown. An immunohistochemical study on chorionic villi samples (CVS) demonstrated that FMRP is completely absent at 12.5 FIG.…”
mentioning
confidence: 96%